E-Cigarettes and Oral Health: A Comprehensive Approach to Prevention Strategies Across Different Levels (Update Dental College Journal, 2025)
Introduction: E-cigarettes are gaining wide acceptance globally and are also posing a serious threat to people's health, especially oral health. Methods: This literature review was performed to review the existing literature using the PubMed, Scopus, and Web of Science databases.  Result: Regarding the effect of e-cigarettes on oral health and potential prevention approaches for all levels of prevention. Conclusion: The review will shed light on the knowledge gaps and the need for further research.Update Dent. Coll. j: 2025; 15(1): 52-55